Surface interaction of doxorubicin with anatase determines its photodegradation mechanism: insights into removal of waterborne pharmaceuticals by TiO2 nanoparticles. Issue 4 (21st March 2018) - Curry, Dennis E.; Andrea, Kori A.; Carrier, Andrew J.; Nganou, Collins; Scheller, Hope; Yang, Dongchang; Youden, Brian; Zhang, Youwei; Nicholson, Amanda; Cui, Shufen; Oakes, Ken D.; MacQuarrie, Stephanie L.; et al.
Abstract : Adsorption of pharmaceuticals on anatase nanoparticles determines the rate and intermediates formed during photodegradation. Abstract : Titanium dioxide (TiO2 ) nanomaterials are extensively used in environmental and energy research. However, their utility is governed by surface interactions with surrounding environments and molecules. A deep understanding of these interactions is critical for the development of advanced TiO2 applications. Herein, we systematically investigate the adsorption of doxorubicin (DOX), a highly toxic chemotherapeutic and model antibiotic pharmaceutical, onto anatase TiO2 nanoparticles and correlate the photodegradation mechanism of DOX with its surface adsorption. Compared to the photodegradation of non-adsorbed species in solution by mobile hydroxyl radicals, the adsorption-dependent surface oxidation by UV-induced holes on TiO2 is more efficient. This study underscores the importance of controlling surface adsorption within photodegradation applications via pH alteration, which would be highly relevant for photo-oxidative remediation of environmental organic pollutants with amine or carbonyl functionalities that chemisorb on titania surfaces.